Perlindungan Hukum Terhadap Buruh dalam Praktik Penahanan Ijazah oleh Perusahaan di Indonesia - Kearen Elvira Naftali; Gunardi Lie (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This practice is essentially based on clauses in employment contracts intended to prevent employees from resigning before the contract term expires. However, from a legal perspective, this practice raises challenges regarding the validity of employment contracts and the legal protections afforded to employees. The objective of this study is to evaluate the validity of the diploma retention practice through the lens of labor law and civil law, as well as to explore the types of legal protections that may be available to employees. The research methodology employed is a normative legal approach, utilizing a legal and conceptual framework, and supported by a literature review of primary and secondary legal sources. This analysis emphasizes the principles of contract law, labor protection principles, and relevant human rights standards. The research findings indicate that the practice of withholding diplomas lacks a clear legal basis under Indonesian law and potentially violates the criteria for the validity of contracts, particularly regarding the abuse of circumstances (misbruik van omstandigheden). Furthermore, this practice can be categorized as an illegal act because it infringes upon workers’ property rights and their freedom to seek employment. Legal protection for workers can be facilitated through preventive strategies, such as strengthening labor regulations and oversight, as well as through enforcement actions, including civil litigation and the resolution of industrial disputes.